Beneficial Immune Effects of Myeloid‐Related Proteins in Kidney Transplant Rejection. Issue 5 (1st February 2016) - Rekers, N. V.; Bajema, I. M.; Mallat, M. J. K.; Petersen, B.; Anholts, J. D. H.; Swings, G. M. J. S.; van Miert, P. P. M. C.; Kerkhoff, C.; Roth, J.; Popp, D.; van Groningen, M. C.; Baeten, D.; et al.
Abstract : Acute rejection is a risk factor for inferior long‐term kidney transplant survival. Although T cell immunity is considered the main effector in clinical acute rejection, the role of myeloid cells is less clear. Expression of S100 calcium‐binding protein A8 (S100A8) and S100A9 was evaluated in 303 biopsies before and after transplantation from 190 patients. In two independent cohorts of patients with acute rejection (n = 98 and n = 11; mostly cellular rejections), high expression of S100 calcium‐binding protein A8 (S100A8) and A9 (S100A9) was related to improved graft outcome. Mechanisms of action of the S100 molecules were investigated. In the graft and peripheral blood cells, S100A8 and S100A9 expression correlated with myeloid‐derived suppressor markers. In line with this finding, recombinant S100A8 and S100A9 proteins inhibited maturation and the allogeneic T cell stimulatory capacity of dendritic cells. S100A9 enhanced the production of reactive oxygen species by macrophages, which suppressed T cell activity at low concentrations in the form of hydrogen peroxide. Intragraft S100A8 and S100A9 expression linked to reduced expression of T cell immunity and tissue injury markers and higher expression of immune regulatory molecules. This study sheds new light on the importance of myeloid cell subsets in directing the outcome of T cell–mediated acute rejection. Abstract : The authors find an association between levels of S100 calcium‐binding proteins A8 and A9 during acute kidney transplant rejection with graft outcome, and that these myeloid cell–expressed proteins have immunoregulatory effects toward T cells.